Factor Affecting Capital Adequacy: Major Factor for Bank to Develop Business Growth in Indonesia in 2013-2017 - Novia Rachmawati (IPTEK Journal of Proceedings Series, 2020)
Capital adequacy is a major factor for a bank to be able to develop its business growth. The level of capital adequacy of banks in Indonesia is far above from average CAR of banks in the ASEAN region and peer groups. The high level of capital adequacy in Indonesia is a cautious response from banks in lending amidst from the weak growth of Risk Weighted Assets (RWA). This study aims to determine the effect of non-performing loans (NPLs), Working Capital to Total Assets Ratio (WCTA), Operational Costs / Operating Income (BOPO), Good Corporate Governance (GCG) and Return on Assets (ROA) on the Bank's capital adequacy National Private Public in Indonesia. In this study, the population was used as the object of research was the National Private Commercial Bank listed on the Indonesia Stock Exchange. The sample in this study was taken by pooling data, which is a combination of time series and crosssection during the period of 2013 to 2017. Data were analyzed using Multiple Regression analysis accompanied by a classic assumption test. The results show that there are Non Performing Loan (NPL) and Good Corporate Governance variables did not significantly influence the Capital Adequacy Ratio (CAR) of national private banking companies. And Test results show that there are Working Capital to Total Assets Ratio (WCTA), Operating Costs / Operating Income (BOPO) and Return On Assets (ROA) have a significant positive effect on Capital Adequacy Ratio (CAR) in national private banking companies. This finding is expected to improve the performance of capital adequacy bank from National Private Public in Indonesia.